Automated Disease Diagnosis Using Image Microscopy - Bhanushali, Akshay; Katale, Ashwin; Bandal, Kuldeep; Barsopiya, Vivek; Potey, Manish (International Journal of Computer Sciences and Engineering, 2025)
The finding of sicknesses utilizing microscopy is basic for medicinal services, and exact forecast. The count of WBC and RBC Cells are very important for the doctor to diagnose various diseases such as anemia, leukemia etc. At present, it requires a tremendous measure of human and financial assets. Hardware solutions like Automated Hematology Counter exits, they are very expensive machines and unaffordable in every hospital laboratory. To overcome these problems, this paper proposes an image processing technique to count the number of red blood & white blood cells in the blood sample image. Our methodology has been to consolidate the all-around created field of advanced imaging, image handling, and manual microscopy to acquire a powerful and minimal effort gadget. We utilize a low cost optical microscope retrofitted with computer controlled imaging and stage positioning modules, and perform MATLAB based image processing on the microscopic images to accomplish the wanted results. The blood cell count that is RBC & WBC count is then used to diagnose the patient as well as detection of abnormalities like leukemia. The "Automated Disease Diagnosis Using Image Microscopy" puts to utilize different parts of Electronics and Telecommunication, essentially Circuit Design and Image Processing for the execution of the undertaking.